Population status, management and morphological characteristics of Ramnad White sheep - T. Ravimurugan; N. Kumaravelu; P.Devendran; M.Chellapandian (Journal of Livestock Biodiversity, 2025)
Tamil Nadu state of India is gifted with eight sheep breeds. Ramnad White breed of sheep has unique economic cum cultural importance with special adaptation characteristics to the drought prone areas. The present study was conducted to evaluate the present scenario of Ramnad white sheep in its home tract. A survey was conducted during 2008 in southern districts (Ramanathapura, Sivaganga, Madurai, Virudhunagar, Tirunelveli and Thoothukudi) of TamilNadu state. The pure stock of Ramnad White sheep appears to be sporadically distributed in Aruppukottai and Sivakasi blocks of Virudhunagar district and Vasudevanallur block of Tirunelveli district. Body colour is predominantly milky white. Black rings around the eye and mouth are typically noticed. Further black colour is seen in switch of the tail, areas of knee joint, hock joint, pastern joint (up to hoof) and in the tip of preputial sheath of males. The least squares means for body weight, height at withers, body length, heart girth, paunch girth, face length, ear length and tail length were 31.05 ± 0.57 kg, 74.22 ± 0.71, 66.82 ± 0.87, 81.65 ± 0.82, 72.43 ± 1.15, 24.35 ± 0.74, 12.79 ± 0.28 and 7.84 ± 0.25 cm, respectively in males and 23.50 ± 0.27 kg, 69.88 ± 0.33, 59.19 ± 0.41, 73.44 ± 0.39, 69.96 ± 0.54, 18.23 ± 0.35, 12.27 ± 0.13, 7.81 ± 0.12 cm, respectively in females.